KINERJA BANK UMUM KONVENSIONAL DI ERA REFORMASI - Ai Lutfi Hidayat, Raden (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
Banking institutions are one pillars of the country's economy. His role as a regulator of financial traffic is the cause. Therefore, banks cannot fail, especially bankruptcy. The impact is triggering inflation and deflation that disrupt the economic system and crisis. A bitter experience occurred in 1998. The state suffered losses and triggered a social crisis. Since then, Indonesia has continued to maintain banking institutions to remain healthy and stable. This study aims to present information on banking performance, so it can be useful for parties. Proof efforts use a quantitative approach. Research data sourced from OJK. The results showed that the bank's performance was relatively good. But the last ten years showed a downward trend. The bank is able to maintain capital adequacy, good management of credit burden and risk, so as to increase interest income. But this has not been able to optimize profit and liquidity